XIII—Knowing How to Reason Logically. Issue 3 (9th September 2021) - Besson, Corine
Abstract: In this paper, I examine Gilbert Ryle's claim that ordinary competence with logical principles or rules is a kind of knowing how, where such knowledge is understood as a skill, a multi-track disposition. Ryle argues that his account of ordinary logical competence helps avoid Lewis Carroll's famous regress argument (Carroll 1895), which suggests that elementary deductive reasoning might be impossible. Indeed, Carroll's regress is the central motivation for Ryle's account. I argue that this account is inadequate on two counts: it cannot serve to articulate the way ordinary reasoners might exercise their knowledge in reasoning and it does not do much to help us avoid Carroll's regress. I sketch an alternative view, still Rylean in spirit, that fares better on both counts.